Monitoring of soil moisture and temperature distributions in seasonally frozen ground with fiber optic sensors. Issue 4 (October 2021) - Zhu, H-H; Wu, B; Cao, D-F; Zhang, C-X; Shi, B
Abstract: The evolution of moisture and temperature fields plays an important role in governing soil behavior, which heavily influences the performance of infrastructures built on the ground soil. However, conventional geotechnical instrumentation presents many limitations in the monitoring of seasonally frozen soils in cold regions. This study investigates the feasibility of actively heated fiber Bragg grating (AH-FBG) in measuring the temperature, water content, and ice content of seasonally frozen soil through laboratory tests and field monitoring. The working principle of the AH-FBG monitoring system is introduced in detail. A series of laboratory calibration tests were performed on soil specimens to explore its performance. Long-term in-situ monitoring was carried out on the Loess Plateau in northwestern China. Results show that the AH-FBG technique can be applied to measure the total water content of soils using the Côté and Konrad model. In the field monitoring, the freezing-thawing process of frozen soil was captured by measuring soil temperatures and ice contents during field monitoring, and the maximum freezing depth was deduced. The AH-FBG technique is verified to be a powerful tool in estimating the actual behavior of in-situ ground soil and provides rich information on multi-field interactions in cold regions.